Rural Electrification and Manufacturing Firm Performance in Benin – An Ex-Ante Impact Assessment - Jörg Peters; Colin Vance; Marek Harsdorff (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Productive electricity use is widely believed to contribute to positive impacts of electrification projects. This paper investigates these impacts by comparing the performance of micro manufacturing enterprises in grid-covered and non-covered villages in Northern Benin. Using firm-level data, the empirical analysis employs a Propensity Score Matching. While beneficial impacts are found from firm creation after electrification, firms that existed before actually show a non-significantly inferior performance to their matched counterparts from a non-electrified region. Complementary measures that sensitize firms about the implications of a grid connection are recommended as important features of program design.
Keywords: C21; O14; O22; L69; 330; Impact evaluation; propensity score matching; productive electricity use; Elektrizitätspolitik; Wirkungsanalyse; Ländlicher Raum; Kleinindustrie; Unternehmensentwicklung; Benin